(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we consider explicit representations and convergence of Hermite- Lagrange Interpolation on two disjoint sets of nodes, which are obtained by projecting vertically the zeros of (1- x2) Pn (? ,? ) (x) and Pn ( ? ,? )(x) respectively on the unit circle, where Pn( ?, ?) (x) stands for Jacobi polynomials.